Simplex Crumbs Homologue 1 Maculopathy Masquerading as Juvenile X-Linked Retinoschisis in Male Patients. (October 2020) - Oh, Daniel J.; Sheth, Veeral; Fishman, Gerald A.; Grassi, Michael A.
Purpose: We demonstrate that Crumbs homologue 1 ( CRB1 ) maculopathy should be considered in the differential of petaloid pigmentary changes in the macula of young children with good vision who may be asymptomatic. Methods: We report on 2 unrelated male patients presenting at a young age with decreased vision from a macular dystrophy due to biallelic CRB1 mutations. Results: In addition to a previously described pathogenic variant, Ile167Gly169del, 2 new pathogenic missense variants in CRB1, Thr745Met and Cys948Tyr, are reported here. Conclusions: Although CRB1 mutations have been more commonly described in retinitis pigmentosa and Leber congenital amaurosis, we demonstrate that mutations in CRB1 can cause a maculopathy in which initial features can resemble juvenile X-linked retinoschisis. We show that the accompanying macular edema is responsive to carbonic anhydrase inhibitors. With long-term follow-up for each case, we illustrate the natural history of CRB1 maculopathy based on clinical examination and diagnostic imaging.